Effectiveness of reminiscence therapy versus cognitive stimulation therapy in older adults with cognitive decline: a quasi-experimental pilot study - Gil, Isabel (2022)
Cognitive impairment can represent a predecessor to neuro-degenerative processes; however, evidence suggests that non-pharmacologic interventions such as reminiscence therapy (RT) and cognitive stimulation therapy (CST) can potentially stabilize or reverse this trend. Community-based settings are widely regarded as the key area of intervention by healthcare professionals in this field. Thus, this study aimed to assess the effects of an RT and a CST program in the cognition, depressive symptomatology, and quality of life (QoL) of older adults with cognitive decline who attend community support structures (CSS) in central Portugal. A quasi-experimental study with two arms (RT and CST program) was conducted for seven weeks. Participants were allocated to each arm based on the CSS they attended. Of the 109 older adults initially screened, 76 completed the intervention (50 in the RT program and 26 in the CST program). A pre- and post-intervention analysis showed statistically significant differences in older adults' cognition, especially in their delayed recall ability, in both groups. Older adults in the RT program evidence improved QoL scores post-intervention. Both the RT and CST programs implemented throughout the study are beneficial to older adults' cognitive performance, although results are more pronounced in the earlier stages of cognitive decline. Participation in the RT program was associated with improvements in older adults' QoL scores.